The age of detrite zircon from metasedimentary rocks of the Ternuvate strata (West Azov block of the Ukrainian Shield) - Artemenko, G.V.; Shumlyanskyy, L.V.; Dovbysh, L.S. (Доповіді НАН України, 2023)
The Ternuvate strata comprise metamorphic rocks that make up the Haichur arcuate structure, which is about 72 km long. Its western part lies within the Andriivka fault zone, which separates the Vovcha and Huliaipole blocks, while the eastern part is located within the Ternuvate fault zone, traced on the Remivka block. The rocks composing the Haichur structure have irregular and laterally variable composition, changeable thickness, and exhibit dynamometamorphic structures of boudinage and schistosity. The upper part of the Ternuvate strata mainly consists of metasedimentary rocks, including gneisses, biotite schists, garnet-biotite, magnetite-amphibole, and feldspar quartzites. The lower part comprises volcanogenic rocks such as amphibolites, metaultrabasites, and biotite-amphibole gneisses. Using the LAICP- MS method, 38 zircon crystals from muscovite-biotite gneisses in the upper part of the Ternuvate strata were analyzed. Based on the geochemical data, these zircons are metamorphosed graywackes. The zircon crystals belong to several age populations (3.65-3.45 and 3.3-2.95 Ga), corresponding to the major stages of Archean crust formation in the West Azov domain, including the formation of the oldest basement and granite-greenstone complexes of the Paleoarchean and Mesoarchean ages. Identical populations of detrital zircon were found in the early Precambrian metaterrigenous rocks of the Krutobalka Formation in the Sorokyne greenstone structure. The correspondence between the Paleoarchean crust (3.45-3.65 Ga) of the West Azov block of the Ukrainian Shield and the Kursk-Besedine granulitegneiss area of the Kursk Magnetic Anomaly block is evident, while the Paleoarchean and Mesoarchean complexes (2.9- 3.3 Ga) correspond to the Mykhailivka and Orel-Tim granite-greenstone area of the Kursk Magnetic Anomaly block. The Archean complexes of Sarmatia are of the same age as similar formations in the Kaapvaal craton in South Africa, Bastar craton in India, North China Craton, Slave craton in Canada, and others, which formed during the Eoarchaean.